الدفع بعدم الدستورية في ظل احكام القانون العضوي 16/18 - صغير, حليم (جامعة الوادي University of Eloued, 2019)
"أنشأ التعديل الدستوري الجديد لسنة 2016 نظاما قضائيًا جديداً ؛ يجسد الدفع بعدم الدستورية في الحالات التي يُدَّعى فيها ، أن هناك نصًا تشريعًا ينتهك الحقوق والحريات التي يكفلها الدستور ، حيث يُعتبر الوصول الممنوح للمدعى عليه للطعن في توافق القوانين مع الضمانات الأساسية بمثابة وسيلة انتصاف حقيقية وفعالة تتكيف مع جبر انتهاك حقوق الإنسان التي يدعي مقدم الطلب أنه ضحية بالمعنى المقصود في المادة (2) من القانون العضوي رقم 18/16 المحدد لشروط و كيفيات تطبيق الدفع بعدم الدستورية ؛فالدافع المتزايد والمكثف لطلبات الدفع بعدم الدستورية وبشكل متزايد يعبئ الجهاز القضائي بأكمله من أجل إعادة النظر في النظام القانوني القائم على تفسير الحقوق والحريات الأساسية ، حيث يساهم فيه الجهاز القضائي بأكمله ، و ذلك من خلال اتخاذ قرار مسبق بمدى أهمية وجدية أو حداثة وسائل عدم الدستورية والتحقق من أن طلب الدفع لم يتم الحصول عليه بالفعل ، فهي آلية إجرائية جديدة ، في سياق الإجراءات المرفوعة أمام محكمة قضائية أو إدارية ، والتي تسمح بالوصول الخاضع للرقابة من قبل أي شخص إلى المجلس الدستوري.. حدد نظام هذه الطريقة الجديدة للإحالة إلى المجلس الدستوري على أن هذا الحق يقود القاضي الدستوري إلى إتقان تقنياته الرقابية ووضع اتفاقيات إجرائية في هامش النص الذي يتهك الحقوق و الحريات ذات القيمة الدستورية،أين يتم إلغاء هذا الحكم من واقع وتاريخ قراره- قرار المجلس الدستوري - و بالتالي فإن الجزاء موضوعي بحد ذاته انتصافاً للحقوق و الحريات ؛ ومع ذلك،فإن المجلس الدستوري لديه إمكانية تعدي ل عواقب عدم الدستورية المعلنة،إما عن طريق تأجيل الإلغاء أو عن طريق تحديد الشروط و الحدود التي من المحتمل أن يتم الطعن فيها في الآثار الناتجة عن هذا الحكم استناد النص المادة (1/2/191) من الدستور؛ هذا وتُمثل سلطة قرارات المجلس الدستوري ضمان تماسك النظام القضائي الجزائري من خلال وحدة تفسير الدستور ، والإدارة الجيدة للعدالة ، واليقين القانوني والمساواة أمام القانون ، هي من المسائل الأساسية التي تحدد قواعد سير المجلس في هذا الاتجاه، طالما كان الدعم الضروري لقرار من المجلس الدستوري ، وبصرف النظر عن النص قيد النظر ، يكتسب تفسير المجلس للدستور السلطة المخولة له بموجب المادة (188) من الدستور أين يضع قانون السوابق القضائية الجديد هذا التوازن الجديد. "" The new constitutional amendment of 2016 established a new judicial system; it embodies the thrust of unconstitutionality in cases where it is alleged that there is a provision of legislation that violates the rights and freedoms guaranteed by the Constitution, where the defendant's access to challenge the conformity of laws with safeguards is considered to be the basis Act as a real and effective remedy adapted to redress the violation of human rights alleged by the applicant to be a victim within the meaning of article (2) of Organic Act No. 18/16, which is specific to the conditions and modalities for the application of the non-constitutional motion; the increasing and intense motivation of the motions for the payment of unconstitutionality and Increasingly mobilizes the entire judiciary in order to review the legal system based on the interpretation of fundamental rights and freedoms, in which the entire judiciary contributes, by deciding in advance how important, serious or modern the means of unconstitutionality are and verifying that the request for payment has not been obtained by Act, it is a new procedural mechanism, in the context of proceedings before a judicial or administrative court, which permits controlled access by any person to the Constitutional Council. The system of this new method of referral to the Constitutional Council has determined that this right leads the constitutional judge to master his supervisory techniques and to establish procedural agreements in the margins of the text which violates the rights and freedoms of constitutional value, where this provision is repealed from the reality and date of his decision-Council decision Constitutional-thus the sanction is in itself an objective remedy for rights and freedoms; However, the Constitutional Council has the possibility of modifying the consequences of the declared unconstitutionality, either by postponing the revocation or by specifying the conditions and limits that are likely to be challenged in the effects resulting from the Provision based on article (1/2/191) of the Constitution; The power of the decisions of the Constitutional Council to ensure the cohesion of the Algerian judicial system through the unity of interpretation of the Constitution, good administration of justice, legal certainty and equality before the law are key issues that determine the rules of operation of the Council in This trend, as long as the necessary support for a decision of the Constitutional Council, and regardless of the text under consideration, the Council's interpretation of the Constitution acquires the power vested in it under article 188 of the Constitution where the new case law establishes this new balance. "
ماستر.اداري
Keywords: الدفع بعدم الدستورية ؛ الحقوق والحريات ؛المجلس الدستوري؛ النظام القضائي العادي و الاداري؛ الشروط و الاجراءات; constitutional؛ cases where it is alleged؛ violation of human rights alleged